Lithium primary battery
Patent Information
- Application Number
- CN202580020131.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-21
- Filing Date
- 2025-03-19
- Publication Date
- 2026-10-09
AI Technical Summary
[0011]根据本公开,能够抑制锂一次电池的放电末期的由内电阻的上升引起的放电电压的降低。
Smart Images

Figure CN122893180A_ABST
Abstract
Description
[0001] Cross-reference of related applications
[0002] This disclosure claims a priority interest in Japanese Patent Application No. 2024-044815, filed on March 21, 2024, the entire contents of which are incorporated herein by reference. Technical Field
[0003] This disclosure relates to primary lithium batteries. Background Technology
[0004] Lithium-ion primary batteries are used as power sources for many electronic devices due to their high energy density and low self-discharge. Manganese dioxide, for example, is used in the positive electrode of a lithium-ion primary battery. Foil-shaped metallic lithium or lithium alloys are used, for example, in the negative electrode.
[0005] Patent document 1 discloses that in a high-temperature lithium battery that uses fluorinated graphite as the positive electrode, a lithium alloy as the negative electrode, and an ionic liquid as the electrolyte, the lithium alloy used is Li-Al alloy, Li-Mg alloy, Li-B alloy, Li-B-Mg alloy, or Li-Si alloy.
[0006] Prior art literature
[0007] Patent documents
[0008] Patent Document 1: Japanese Patent Application Publication No. 2011-192627 Summary of the Invention
[0009] In primary lithium batteries, resistance sometimes increases and discharge voltage decreases at the end of the discharge period.
[0010] One aspect of this disclosure relates to a lithium primary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein the positive electrode contains Li₂. x MnO2 (0≤x≤0.05), the negative electrode comprises an alloy containing lithium, magnesium and metal element M, wherein the metal element M is selected from at least one of strontium and barium, wherein the lithium content in the alloy is 89% by mass or more, the magnesium content in the alloy is 0.01% by mass or more and 10% by mass or less, and the metal element M content in the alloy is 0.00001% by mass or more and 0.05% by mass or less.
[0011] According to this disclosure, it is possible to suppress the decrease in discharge voltage caused by the increase in internal resistance at the end of the discharge phase of a lithium primary battery.
[0012] The novel features of the invention are set forth in the appended claims, but the composition and content of the invention, together with its other objects and features, can be better understood by referring to the following detailed description of the accompanying drawings. Attached Figure Description
[0013] Figure 1 This is a front view showing a section of a lithium primary battery according to one embodiment of the present disclosure. Detailed Implementation
[0014] The following describes embodiments of the present disclosure by way of example, but the present disclosure is not limited to the examples described below. In the following description, specific values and materials are sometimes illustrated, but other values and materials can be applied as long as the effects of the present disclosure are achieved. In this specification, the phrase "value A to value B" includes both value A and value B, and can be interpreted as "value A or higher and value B or lower". In the following description, when lower and upper limits are illustrated for values relating to specific physical properties, conditions, etc., any illustrated lower limit and any illustrated upper limit can be arbitrarily combined as long as the lower limit remains above the upper limit. When multiple materials are illustrated, one can be selected for use alone, or two or more can be used in combination.
[0015] The lithium primary battery disclosed herein includes a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode contains Li. x MnO2 (0 ≤ x ≤ 0.05) is used as the positive electrode active material. The negative electrode comprises an alloy (hereinafter also referred to as "lithium alloy"), which contains lithium (Li), magnesium (Mg) and a metallic element M, wherein the metallic element M is selected from at least one of strontium (Sr) and barium (Ba). The lithium alloy contains 89% by mass or more of Li. The lithium alloy contains 0.01% by mass or more and 10% by mass or less of Mg. The content of metallic element M in the lithium alloy (the combined content of Sr and Ba in the lithium alloy) is 0.00001% by mass or more and 0.05% by mass or less. In the lithium primary battery according to the embodiments of this disclosure, the discharge voltage at the end of the discharge period (e.g., the voltage during pulse discharge in a low-temperature environment) can be improved.
[0016] By incorporating Mg into a Li-containing negative electrode, the strength of the negative electrode is increased, which can suppress the decrease in discharge voltage associated with the formation of cracks and partial defects in the negative electrode at the end of the discharge. On the other hand, since Mg readily alloys with Li, the movement of Li is easily hindered at the end of the discharge, thereby increasing the internal resistance and causing the discharge voltage to decrease.
[0017] Therefore, the inventors conducted in-depth research to suppress the voltage drop at the end of the discharge period, and as a result, they discovered that by including the metal element M in the negative electrode containing Li and Mg, it is possible to suppress the obstruction of Li movement at the end of the discharge period, and to significantly suppress the voltage drop caused by the increase in internal resistance at the end of the discharge period.
[0018] The increased anode strength resulting from the addition of Mg and the inhibition of Li migration in Mg-containing environments by the addition of metal element M complement each other, significantly suppressing the voltage drop at the end of discharge. Furthermore, metal element M also enhances the chemical stability of the film formed on the surface of the lithium alloy (anode) and suppresses side reactions caused by contact between the anode and the non-aqueous electrolyte.
[0019] However, assuming the Mg content in the lithium alloy is greater than 10% by mass, the proportion of Mg in the negative electrode increases, leading to an increase in negative electrode resistance and sometimes a decrease in voltage at the end of discharge. Conversely, assuming the Mg content in the lithium alloy is less than 0.01% by mass, the effect of Mg addition becomes smaller, and sometimes a decrease in voltage occurs at the end of discharge.
[0020] Assuming the content of metallic element M in the lithium alloy is greater than 0.05% by mass, the proportion of metallic element M in the negative electrode increases, thereby increasing the negative electrode resistance and sometimes causing a voltage decrease at the end of discharge. Assuming the content of Mn in the lithium alloy is less than 0.00001% by mass, the effect of adding metallic element M becomes smaller, and sometimes the voltage decreases at the end of discharge.
[0021] Assuming the Li content in the lithium alloy is less than 89% by mass, the proportion of Li in the negative electrode becomes smaller, which sometimes leads to a decrease in discharge voltage.
[0022] (Lithium alloy)
[0023] Lithium alloys contain Li, Mg, and the metallic element M. From the perspective of reducing internal resistance and ensuring capacity, the Li content in lithium alloys is 89% by mass or higher, and can be 90% by mass or higher, or 95% by mass or higher. The Li content in lithium alloys can be below 99.98999% by mass. In lithium alloys, elements other than Mg and the metallic element M can be Li.
[0024] From the viewpoint of improving the strength of the negative electrode, the Mg content in the lithium alloy is 0.01% by mass or more, preferably 0.05% by mass or more, more preferably 0.1% by mass or more or 0.2% by mass or more, and can be 1% by mass or more. From the viewpoint of reducing the resistance of the negative electrode, the Mg content in the lithium alloy is 10% by mass or less, preferably 8% by mass or less, more preferably 7% by mass or less or 4% by mass or less. The range of Mg content in the lithium alloy can be, for example, 0.2% by mass or more and 7% by mass or less, and can be 1% by mass or more and 4% by mass or less.
[0025] Lithium alloys contain Sr and / or Ba as the metallic element M. From the viewpoint of suppressing voltage drop at the end of discharge, lithium alloys preferably contain both Sr and Ba. In this case, the mass ratio of Sr to Ba in the lithium alloy (Sr / Ba) can be 40 / 60 or higher and 60 / 40 or lower.
[0026] From the viewpoint of suppressing voltage drop at the end of discharge, the content of metal element M in the lithium alloy is 0.00001% by mass or more, preferably 0.00002% by mass or more, more preferably 0.0001% by mass or more, or 0.0004% by mass or more. From the viewpoint of reducing negative electrode resistance, the content of metal element M in the lithium alloy is 0.05% by mass or less, preferably 0.01% by mass or less, more preferably 0.005% by mass or less. The range of the content of metal element M in the lithium alloy can be, for example, 0.00002% by mass or more and 0.05% by mass or less, 0.0001% by mass or more and 0.01% by mass or less, or 0.0004% by mass or more and 0.01% by mass or less. The molar ratio of metal element M to Mg, M / Mg, can be, for example, in the range of 0.000001 to 0.5.
[0027] Lithium alloys can also contain other metallic elements besides Li, Mg, and M. Examples of other metallic elements include Al, Sn, Ni, Pb, In, Na, K, and Ca. The composition of lithium alloys can be determined using inductively coupled plasma atomic emission spectrometry (ICP) or atomic absorption spectrometry (AAS).
[0028] The lithium alloy preferably also contains Al. A portion of the Mg contained in the lithium alloy can be replaced with Al. In this case, the voltage drop at the end of discharge can be further suppressed. The exact reason is not yet clear, but it is speculated that by adding Al, it is easy to form a region where Al and the metallic element M condense. Near this region, Li is difficult to alloy with Mg, thus further suppressing the obstruction of Li migration at the end of discharge when Mg is included. Furthermore, it is speculated that when Al is included along with Mg and the metallic element M, a low-resistivity film can be easily and stably formed.
[0029] From the viewpoint of suppressing voltage drop at the end of discharge, the Al content in the lithium alloy can be 0.01% by mass or more and 10% by mass or less, preferably 0.01% by mass or more (or 0.1% by mass or more) and 5% by mass or less, and more preferably 0.1% by mass or more and 2% by mass or less.
[0030] From the same perspective, the combined content of Mg and Al in the lithium alloy is preferably 0.02% by mass or more and 10% by mass or less, more preferably 0.2% by mass or more and 4% by mass or less. Approximately half the mass of Mg can be replaced with Al. The molar ratio of Al to Mg, Al / Mg, can, for example, be in the range of 0.01 to 45.
[0031] (Additives for non-aqueous electrolytes)
[0032] The non-aqueous electrolyte preferably contains at least one additive selected from cyclic imide compounds, phthalate compounds, and isocyanate compounds. When the non-aqueous electrolyte contains the above-mentioned additives, a composite film can be formed on the surface of the lithium alloy (anode), the composite film containing components derived from the lithium alloy (Mg, metal element M) and components derived from the additives. By forming such a composite film, the increase in internal resistance and the associated voltage drop at the end of discharge can be further suppressed. Since the composite film contains Mg and metal element M, the anode resistance (reaction resistance) is reduced. Furthermore, the composite film exhibits excellent chemical stability, thus protecting the lithium alloy with a high-quality composite film.
[0033] The content of additives in the non-aqueous electrolyte is, for example, 0.01% by mass or more and 5% by mass or less. Furthermore, the content of additives in the non-aqueous electrolyte is the mass ratio (percentage) of the additives relative to the total mass of the non-aqueous electrolyte. For example, immediately after battery manufacturing (or during non-aqueous electrolyte preparation), the content of additives in the non-aqueous electrolyte is preferably within the above-mentioned range. In contrast, in batteries that have been in use for a certain period after manufacturing, some of the additives are consumed during the formation of the coating, and the content of additives in the non-aqueous electrolyte may be a value smaller than the above-mentioned range. In this case, even if the content of additives in the non-aqueous electrolyte is small (e.g., close to the detection limit), the aforementioned effects brought about by the additives can be confirmed. The same applies to the content of various compounds such as cyclic imide compounds described later.
[0034] (Cyclic imide compounds)
[0035] Examples of cyclic imide compounds include cyclic diacylamine compounds. A cyclic imide compound only needs to have a diacylamine ring (hereinafter also referred to as an imide ring). Other rings (hereinafter also referred to as a second ring) may be condensed on the imide ring. Cyclic imide compounds can be contained in the imide state in a non-aqueous electrolyte, or they can be contained in the form of anions or salts. When a cyclic imide compound is contained in the imide state in a non-aqueous electrolyte, it can be contained in the form of a free NH group, or it can be contained in the form of a tertiary amine.
[0036] Examples of the second ring include aromatic rings, saturated or unsaturated aliphatic rings, etc. The second ring may also contain at least one heteroatom. Examples of heteroatoms include oxygen atoms, sulfur atoms, and nitrogen atoms.
[0037] Examples of cyclic imide compounds include aliphatic dicarboxylic acid imide compounds and cyclic imide compounds having a second ring. Examples of aliphatic dicarboxylic acid imide compounds include succinimide. Examples of cyclic imide compounds having a second ring include imide compounds of aromatic or alicyclic dicarboxylic acids. Examples of aromatic or alicyclic dicarboxylic acids include compounds having carboxyl groups on two adjacent atoms forming the ring. Examples of cyclic imide compounds having a second ring include phthalimide and hydrogenated phthalimide. Examples of hydrogenated phthalimide are cyclohexyl-3-ene-1,2-dicarboximide and cyclohexane-1,2-dicarboximide.
[0038] The imide ring can also be an N-substituted imide ring with a substituent on the nitrogen atom of the imide. Examples of such substituents include hydroxyl, alkyl, alkoxy, and halogen atoms. Examples of alkyl groups include C1-C4 alkyl groups such as methyl and ethyl. Examples of alkoxy groups include C1-C4 alkoxy groups such as methoxy and ethoxy. Examples of halogen atoms include chlorine and fluorine atoms.
[0039] The cyclic imide compound is preferably selected from at least one of phthalimides and N-substituted phthalimides. The substituent on the nitrogen atom of the N-substituted phthalimide can be selected from substituents exemplified with respect to the N-substituted imide ring. The N-substituted phthalimide preferably comprises, for example, at least one selected from N-hydroxyphthalimide, N-(2-hydroxyethyl)phthalimide, N-(cyclohexylthio)phthalimide, and N-(phenylthio)phthalimide. The phthalimide and / or N-substituted phthalimide may constitute 50% or more by mass of the cyclic imide compound, and further may constitute 70% or more by mass or 90% or more by mass.
[0040] The non-aqueous electrolyte may contain one or more cyclic imide compounds. The content of cyclic imide compounds in the non-aqueous electrolyte may be less than 1% by mass, more than 0.001% by mass and less than 1% by mass, or more than 0.001% by mass and less than 0.8% by mass.
[0041] (Phthyl ester compounds)
[0042] Phthalate ester compounds include phthalates and their derivatives. Derivatives may have substituents linked to an aromatic ring derived from phthalic acid. Examples of such substituents include hydroxyl, alkyl, alkoxy, and halogen atoms. Examples of alkyl groups include C1-C4 alkyl groups such as methyl and ethyl. Examples of alkoxy groups include C1-C4 alkoxy groups such as methoxy and ethoxy. Examples of halogen atoms include chlorine and fluorine atoms.
[0043] Phthalate ester compounds can be monophthalic acid ester compounds, but from the viewpoint that the resulting coating easily protects the Li alloy surface, diphthalic acid ester compounds are preferred. As the alcohol that forms an ester with phthalic acid (or its derivatives), saturated or unsaturated aliphatic alcohols of C1 to C20 (preferably C1 to C6) are preferred.
[0044] Specific examples of phthalate diester compounds include dimethyl phthalate, diethyl phthalate, diallyl phthalate, dibutyl phthalate, diisobutyl phthalate, and bis(2-ethylhexyl) phthalate. They can be used alone or in combination of two or more. The phthalate diester compound can constitute 50% or more by mass of the phthalate ester compound, and further can constitute 70% or more or 90% or more by mass.
[0045] The non-aqueous electrolyte may contain one phthalate compound or two or more phthalate compounds. The content of phthalate compounds in the non-aqueous electrolyte may be less than 1% by mass or more than 0.1% by mass and less than 1% by mass.
[0046] (Isocyanate compounds)
[0047] Isocyanate compounds, for example, have at least one isocyanate group and a C1-C20 aliphatic hydrocarbon group or a C6-C20 aromatic hydrocarbon group. The aliphatic hydrocarbon group and aromatic hydrocarbon group constituting the isocyanate compound may also have substituents. Substituents can be any stable group, such as a halogen atom or a nitrile group. The aliphatic group can be an alicyclic aliphatic group, or a straight-chain or branched aliphatic group. The aromatic hydrocarbon group is a hydrocarbon group having one or more aromatic rings, and can be a group in which an aromatic ring and an aliphatic group are linked.
[0048] The isocyanate compound can be a monoisocyanate compound having one isocyanate group, but it is preferably a diisocyanate compound having two isocyanate groups. It is believed that diisocyanate compounds form composite films with higher chemical stability compared to monoisocyanate compounds, and composite films with lower resistivity compared to triisocyanates. Furthermore, even in small amounts, diisocyanate compounds have a high ability to form composite films and exhibit excellent stability within the battery.
[0049] As a specific example of a diisocyanate compound, one could cite OCN-C n H 2n Compounds represented by -NCO (where n is an integer from 1 to 10) (e.g., hexamethylene diisocyanate), compounds having an alicyclic dimethyl group (e.g., 1,3-bis(isocyanate methyl)cyclohexane, dicyclohexylmethane-4,4'-diisocyanate, bicyclo[2.2.1]heptane-2,5-dimethylbis(methyl)isocyanate, bicyclo[2.2.1]heptane-2,6-dimethylbis(methyl)isocyanate, isophorone diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, hexyl isocyanate, etc.). Preferably, at least one is selected from hexamethylene diisocyanate, 1,3-bis(isocyanate methyl)cyclohexane, and isophorone diisocyanate. They may account for 50% or more by mass of the isocyanate compound, and further may account for 70% or more by mass or 90% or more by mass of it.
[0050] When diisocyanate compounds are added to a non-aqueous electrolyte, these compounds react with each other within the battery (in the non-aqueous electrolyte) to form isocyanurates, ureas, or biuret esters. Therefore, when analyzing the non-aqueous electrolyte by disassembling the battery, isocyanurates, ureas, or biuret esters derived from diisocyanate compounds are sometimes detected.
[0051] The non-aqueous electrolyte may contain one or more isocyanate compounds. The content of isocyanate compounds in the non-aqueous electrolyte may be less than 3% by mass, more than 0.01% by mass and less than 2% by mass, or more than 0.01% by mass and less than 1.5% by mass.
[0052] In the analysis of non-aqueous electrolytes (additives), liquid chromatography-mass spectrometry (LC / MS) and gas chromatography-mass spectrometry (GC / MS) can be used, for example. Ultraviolet spectroscopy (UV) analysis can also be performed in conjunction with nuclear magnetic resonance (NMR), infrared absorption spectroscopy (IR), and mass spectrometry (MS).
[0053] The lithium primary battery of this disclosure will now be described in more detail.
[0054] [Lithium primary battery]
[0055] (positive electrode)
[0056] The positive electrode contains a positive electrode additive. This additive includes manganese dioxide as the active material. Positive electrodes containing manganese dioxide exhibit higher voltage and excellent pulse discharge characteristics. Preferably, the manganese dioxide used is obtained by sintering electrolytic manganese dioxide. The manganese dioxide can be in a mixed crystal state containing various crystalline states. The positive electrode may also contain manganese oxides other than manganese dioxide. Examples of manganese oxides other than manganese dioxide include MnO, Mn3O4, Mn2O3, and Mn2O7. The main component of the manganese oxides contained in the positive electrode is preferably manganese dioxide.
[0057] The manganese dioxide in the positive electrode can also be doped with a small amount of lithium. If the lithium doping level is small, high capacity can be ensured. Manganese dioxide and manganese dioxide doped with a small amount of lithium can be used with Li... x MnO2 (0≤x≤0.05) is used. Furthermore, the overall average composition of the manganese oxide in the positive electrode only needs to be Li. x MnO2 (0 ≤ x ≤ 0.05) is sufficient. Furthermore, the Li ratio x only needs to be below 0.05 in the initial discharge state of the lithium primary battery. The Li ratio x generally increases as the lithium primary battery discharges. Theoretically, the oxidation state of manganese in manganese dioxide is tetravalent. However, by including other manganese oxides in the positive electrode or doping manganese dioxide with lithium, the oxidation state of manganese can sometimes slightly increase or decrease from tetravalent. Therefore, in Li... x In MnO2, the average oxidation number of manganese is allowed to increase or decrease slightly from valence 4.
[0058] Positive electrode, except for Li xIn addition to MnO2, other positive electrode active materials suitable for use in lithium primary batteries may be included. Examples of other positive electrode active materials include fluorinated graphite. The proportion of manganese dioxide in the total positive electrode active material is preferably 90% by mass or more.
[0059] Electrolytic manganese dioxide is preferably used as the manganese dioxide. Adjusting the calcination conditions can increase the crystallinity of the manganese dioxide and decrease its specific surface area. Li x The BET specific surface area of MnO2 can be 5m². 2 / g or more and 40m 2 / g or less. In Li x When the BET specific surface area of MnO2 is within the above range, it can suppress self-discharge and further suppress the decrease in pulse discharge characteristics after storage.
[0060] Li x The BET specific surface area of MnO2 can be determined using known methods, such as a specific surface area measuring device (e.g., manufactured by MOUNTECH Co., Ltd.) based on the BET method. For example, the Li2O3 separated from the positive electrode of the self-contained cell can be used as a specific surface area. x MnO2 can be used as the test sample.
[0061] Li x The median particle size of MnO2 can be greater than 5 μm and less than 40 μm. When the median particle size is within the above range, self-discharge can be suppressed, and the decrease in pulse discharge characteristics after storage can be further suppressed.
[0062] Li x The median particle size of MnO2 is, for example, the median of the particle size distribution obtained using quantitative laser diffraction-scattering (qLD) method. For instance, this could be achieved by separating the Li from the positive electrode taken from the self-contained cell. x MnO2 can be used as the test sample. For example, the SALD-7500nano manufactured by Shimadzu Corporation can be used in the test.
[0063] In addition to the positive electrode active material, the positive electrode mixture may also contain a binder. The positive electrode mixture may also contain a conductive agent.
[0064] Examples of adhesives include fluoropolymers, rubber particles, and acrylic resins.
[0065] Examples of conductive agents include conductive carbon materials. Examples of conductive carbon materials include natural graphite, synthetic graphite, carbon black, and carbon fiber.
[0066] The positive electrode can further include a positive current collector that retains the positive electrode flux. Materials used for the positive current collector include, for example, stainless steel, aluminum, and titanium.
[0067] In the case of a coin-shaped battery, the positive electrode can be formed by mounting an L-shaped annular positive current collector onto a positive electrode compound sheet, or the positive electrode can be formed solely by the positive electrode compound sheet. The positive electrode compound sheet is, for example, obtained by compressing and drying a moistened positive electrode compound prepared by adding an appropriate amount of water to the positive electrode active material.
[0068] In the case of a cylindrical battery, a positive electrode comprising a sheet-like positive current collector and a positive electrode binder layer held in the positive current collector can be used. The sheet-like positive current collector is preferably a porous current collector. Examples of porous current collectors include expanded metal, net, and punching metal. The positive electrode binder layer is obtained, for example, by coating or filling the sheet-like positive current collector with the aforementioned wetted positive electrode binder, applying pressure in the thickness direction, and then drying.
[0069] The positive electrode preferably comprises a porous current collector as described above and a positive electrode filler filling the current collector. Preferably, a current collector comprising at least one material selected from SUS444, SUS430, and SUS316 is used. By using such a current collector, in a lithium primary battery, side reactions with the aforementioned non-aqueous electrolyte and corrosion of the current collector can be suppressed, as can the increase in internal resistance and gas generation. Particularly when such a current collector is combined with a non-aqueous electrolyte comprising at least one of LiCF3SO3 and LiClO4, which are typically used as lithium salts in lithium primary batteries, side reactions between the current collector and the non-aqueous electrolyte can be suppressed more effectively. The thickness of the positive electrode is, for example, 300 μm or more and 900 μm or less.
[0070] (negative electrode)
[0071] The negative electrode can, for example, comprise a foil-like (sheet-like) lithium alloy. The lithium alloy can be shaped into any shape and thickness depending on the shape, size, specifications, and performance characteristics of the primary lithium battery.
[0072] In the case of cylindrical batteries, the negative electrode can have a negative electrode current collector (e.g., copper foil) carrying a lithium alloy, or it can be a foil (sheet) lithium alloy without a negative electrode current collector. When the lithium alloy contains Mg, the residual Mg strength is relatively high at the end of discharge, so it is possible to construct the negative electrode using only the foil (sheet) lithium alloy without a negative electrode current collector. By using a lithium alloy containing Mg, it is possible to suppress the breakage and partial loss of the negative electrode at the end of discharge when the negative electrode does not contain a negative electrode current collector. The shape of the negative electrode (lithium alloy) can be maintained even at the end of discharge, and the overall conductivity of the negative electrode can be ensured even without using a negative electrode current collector.
[0073] In the case of coin-shaped batteries, a hoop-shaped lithium alloy can be punched into a circular plate and used as the negative electrode. In the case of cylindrical batteries, a sheet-shaped lithium alloy can be used as the negative electrode. The sheet is obtained, for example, by extrusion molding. More specifically, in cylindrical batteries, lithium alloy foils or the like with shapes having a long side direction and a short side direction can be used.
[0074] (Non-aqueous electrolyte)
[0075] As a non-aqueous electrolyte, it can be used in non-aqueous solvents as an electrolyte in which lithium salts are dissolved.
[0076] As non-aqueous solvents, examples of organic solvents commonly used in non-aqueous electrolytes for primary lithium batteries include ethers, esters, and carbonates. Other non-aqueous solvents that can be used include dimethyl ether, γ-butyrolactone, propylene carbonate, ethylene carbonate, and 1,2-dimethoxyethane. Non-aqueous electrolytes may contain one or more non-aqueous solvents.
[0077] From the viewpoint of improving the discharge characteristics of lithium primary batteries, the non-aqueous solvent preferably comprises a cyclic carbonate with a high boiling point and a chain ether with low viscosity even at low temperatures. The cyclic carbonate preferably comprises at least one selected from propylene carbonate (PC) and ethylene carbonate (EC), with PC being particularly preferred. The chain ether preferably has a viscosity of less than 1 mPa·s at 25°C, and dimethoxyethane (DME) is particularly preferred. Furthermore, the viscosity of the non-aqueous solvent is determined by measuring it at 25°C with a shear rate of 10000 (1 / s) using a micro-sample viscometer m-VROC manufactured by RheoSense.
[0078] Examples of lithium salts include LiCF3SO3, LiClO4, LiBF4, LiPF6, LiRaSO3 (Ra is a fluoroalkyl group with 1 to 4 carbon atoms), LiFSO3, LiN(SO2Rb)(SO2Rc) (Rb and Rc are each independently a fluoroalkyl group with 1 to 4 carbon atoms), and LiN(FSO2)2. A single lithium salt can be used, or two or more can be used in combination.
[0079] The concentration of lithium ions (total concentration of lithium salts) in the non-aqueous electrolyte is, for example, above 0.2 mol / L and below 2.0 mol / L, or above 0.3 mol / L and below 1.5 mol / L.
[0080] Non-aqueous electrolytes may also contain additives as needed. Examples of such additives include phthalimides, N-substituted phthalimide compounds, dimethyl phthalate, phthalate ester compounds, propane sulpholactone, and vinylene carbonate. The total concentration of such additives in the non-aqueous electrolyte is, for example, 0.003~5 mol / L.
[0081] (Diaphragm)
[0082] Lithium-ion primary batteries typically have a separator between the positive and negative electrodes. As the separator, any porous sheet formed of an insulating material that is resistant to the internal environment of the lithium-ion primary battery can be used. Specifically, examples include nonwoven fabrics made of synthetic resin, microporous membranes made of synthetic resin, or laminates thereof.
[0083] Examples of synthetic resins used in nonwoven fabrics include polypropylene, polyphenylene sulfide, and polybutylene terephthalate. Examples of synthetic resins used in microporous membranes include polyethylene, polypropylene, and polyolefin resins such as ethylene-propylene copolymers. Microporous membranes may also contain inorganic particles as needed.
[0084] The thickness of the diaphragm is, for example, greater than 5 μm and less than 100 μm.
[0085] The structure of a primary lithium battery is not particularly limited. A primary lithium battery can be a coin-shaped battery having a stacked electrode group consisting of a circular plate-shaped positive electrode and a circular plate-shaped negative electrode separated by a separator. It can also be a cylindrical battery having a wound electrode group consisting of a strip-shaped positive electrode and a strip-shaped negative electrode wound in a spiral shape separated by a separator.
[0086] Figure 1 The diagram shows a front view of a portion of a cylindrical primary lithium battery according to an embodiment of the present disclosure. In the primary lithium battery 10, an electrode group consisting of a positive electrode 1 and a negative electrode 2 wound together with a separator 3 is housed in a battery casing 9 along with a non-aqueous electrolyte (not shown). A sealing plate 8 is installed at the opening of the battery casing 9. A positive electrode lead 4, connected to the current collector 1a of the positive electrode 1, is connected to the sealing plate 8. A negative electrode lead 5, connected to the negative electrode 2, is connected to the casing 9. Furthermore, to prevent internal short circuits, an upper insulating plate 6 and a lower insulating plate 7 are respectively provided above and below the electrode group.
[0087] [Postscript]
[0088] The following technology has been disclosed through the description of the above embodiments.
[0089] (Technology 1)
[0090] A primary lithium battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte.
[0091] The positive electrode contains Li x MnO2 (0≤x≤0.05),
[0092] The negative electrode comprises an alloy containing lithium, magnesium, and a metallic element M, wherein the metallic element M is at least one selected from strontium and barium.
[0093] The lithium content in the alloy is 89% by mass or more.
[0094] The magnesium content in the alloy is 0.01% by mass or more and 10% by mass or less.
[0095] The content of the metallic element M in the alloy is more than 0.00001% by mass and less than 0.05% by mass.
[0096] (Technology 2)
[0097] The lithium primary battery according to technology 1
[0098] The alloy contains aluminum.
[0099] The total content of magnesium and aluminum in the alloy is more than 0.02% by mass and less than 10% by mass.
[0100] (Technology 3)
[0101] The lithium primary battery according to technology 1 or 2
[0102] Li x The median particle size of MnO2 is greater than 5 μm and less than 40 μm.
[0103] (Technology 4)
[0104] The lithium primary battery according to any one of techniques 1 to 3
[0105] Li x The BET specific surface area of MnO2 is 5m². 2 / g or more and 40m 2 / g or less.
[0106] (Technology 5)
[0107] The lithium primary battery according to any one of techniques 1 to 4
[0108] The non-aqueous electrolyte contains at least one additive selected from cyclic imide compounds, phthalate compounds, and isocyanate compounds.
[0109] (Technology 6)
[0110] The lithium primary battery according to technology 5
[0111] The cyclic imide compound comprises at least one selected from phthalimide and N-substituted phthalimide.
[0112] (Technology 7)
[0113] The lithium primary battery according to technology 6
[0114] The N-substituted phthalimide comprises at least one selected from N-hydroxyphthalimide, N-(2-hydroxyethyl)phthalimide, N-(cyclohexylthio)phthalimide, and N-(phenylthio)phthalimide.
[0115] (Technology 8)
[0116] The lithium primary battery according to any one of techniques 5 to 7
[0117] The content of the cyclic imide compound in the non-aqueous electrolyte is less than 1% by mass.
[0118] (Technology 9)
[0119] The lithium primary battery according to any one of techniques 5 to 8
[0120] The phthalate compound includes a phthalate diester compound.
[0121] (Technology 10)
[0122] The lithium primary battery according to technology 9
[0123] The phthalate compound comprises dimethyl phthalate.
[0124] (Technology 11)
[0125] The lithium primary battery according to any one of techniques 5 to 10
[0126] The phthalate compound in the non-aqueous electrolyte is present in a concentration of less than 1% by mass.
[0127] (Technology 12)
[0128] The lithium primary battery according to any one of techniques 5 to 11
[0129] The isocyanate compound includes a diisocyanate compound.
[0130] (Technology 13)
[0131] The lithium primary battery according to technology 12
[0132] The diisocyanate compound comprises at least one selected from hexamethylene diisocyanate, 1,3-bis(isocyanate methyl)cyclohexane, and isophorone diisocyanate.
[0133] (Technology 14)
[0134] The lithium primary battery according to any one of techniques 5 to 13
[0135] The isocyanate compound in the non-aqueous electrolyte is present in an amount of less than 3% by mass.
[0136] [Example]
[0137] The present disclosure is described in detail below based on embodiments and comparative examples, but the present disclosure is not limited to the following embodiments.
[0138] [Batteries A1~A18, Batteries B1~B11]
[0139] (The production of the positive electrode)
[0140] As the positive electrode, 3 parts by mass of Ketjen black as a conductive agent, 5 parts by mass of polytetrafluoroethylene as a binder, and an appropriate amount of pure water were added to 100 parts by mass of calcined electrolytic manganese dioxide and mixed to prepare a wet positive electrode mixture.
[0141] Next, a positive electrode precursor was created by filling a positive electrode current collector made of 0.4 mm thick expanded metal mesh made of stainless steel (SUS444) with a positive electrode filler. Then, the positive electrode precursor was dried, rolled to a thickness of 0.5 mm using a roll press, and cut to the specified dimensions to obtain the positive electrode. Next, a portion of the filled positive electrode filler was peeled off, and one end of a stainless steel positive electrode lead was resistance-welded to the portion exposing the positive electrode current collector.
[0142] (Making the negative electrode)
[0143] The negative electrode is obtained by cutting lithium metal foil or lithium alloy foil (200 μm thick) to a specified size. One end of the nickel negative electrode lead is connected to a specified location on the negative electrode by ultrasonic welding.
[0144] The lithium alloy foil was configured as shown in Tables 1-3. In addition to lithium, the lithium alloy foil also contained the metal elements (Mg, Sr, Ba, and / or Al) shown in Tables 1-3. The content of each metal element in the lithium alloy foil was set to the values shown in Tables 1-3. A "0" in the content column of Tables 1-3 indicates that the content is below the detection limit in compositional analysis (ICP emission spectroscopy, etc.).
[0145] (Fabrication of the electrode group)
[0146] An electrode group was produced by winding a positive electrode and a negative electrode with a separator interposed therebetween. A microporous polypropylene membrane having a thickness of 25 µm was used as the separator.
[0147] (Preparation of Nonaqueous Electrolyte Solution)
[0148] Propylene carbonate (PC), ethylene carbonate (EC) and 1,2-dimethoxyethane (DME) were mixed at a volume ratio of 4:2:4 to obtain a nonaqueous solvent. LiCF₃SO₃ was dissolved in the nonaqueous solvent at a concentration of 0.5 mol / L to prepare a nonaqueous electrolyte solution.
[0149] (Assembly of Primary Lithium Battery)
[0150] The electrode group was housed in a cylindrical battery case that also serves as a negative electrode terminal. An iron case (outer diameter: 17 mm, height: 45.5 mm) was used as the battery case. Subsequently, after injecting the nonaqueous electrolyte solution into the battery case, the opening of the battery case was sealed with a metal sealing plate that also serves as a positive electrode terminal. The other end of the positive electrode lead was connected to the sealing plate, and the other end of the negative electrode lead was connected to the inner bottom surface of the battery case. A cylindrical primary lithium battery was thus produced. The battery immediately after assembly was discharged at 2.4 A for 2 minutes, and then aged for 7 days in an atmosphere at 45°C. Furthermore, the positive electrode active material after aging is represented by the formula Li x MnO₂, wherein the value x representing the doping amount of lithium is in the range of 0 < x ≤ 0.05. In the tables, batteries A1 to A18 are examples, and batteries B1 to B11 are comparative examples.
[0151] Furthermore, the Li contained in the positive electrode mixture x MnO₂ has a median particle diameter of 21 to 23 µm, and a BET specific surface area of 14 to 15 m 2 / g.
[0152] [Evaluation]
[0153] The aged battery was discharged to a depth of discharge (DOD) of 90%. For the battery at the end of discharge, the internal resistance (frequency: 1 kHz) was measured using an AC resistance meter in an environment at 20°C. In addition, the battery at the end of discharge was left standing in an environment at -30°C for 2 hours, then subjected to pulse discharge at 300 mA for 1 second in the environment at -30°C, and the minimum voltage obtained in this process was determined as the pulse discharge voltage.
[0154] The evaluation results are shown in Tables 1 to 3. In Tables 1 to 3, the internal resistance is expressed as a relative value when the internal resistance of Battery B2 is taken as 100. The pulse discharge voltage is expressed as a relative value when the pulse discharge voltage of Battery B2 is taken as 100.
[0155]
[0156]
[0157]
[0158] Batteries A1 to A18 have low internal resistance and high pulse discharge voltage at the end of the discharge period.
[0159] Batteries B1-B4 and B8-B9 exhibit reduced voltage at the end of discharge due to the use of Li metal foil or Li alloy foil without Mg and / or the metallic element M as the negative electrode. Battery B5, although using Li-Mg-Sr-Ba alloy foil, suffers from reduced voltage at the end of discharge because the Mg content exceeds 10% by mass. Batteries B6-B7, while using Li-Mg-Sr-Ba alloy foil, experience reduced voltage at the end of discharge because the combined Sr and Ba content is less than 0.00001% by mass or more than 0.05% by mass. Batteries B10-B11, while using Li-Mg-Sr-Ba-Al alloy foil, suffer from reduced voltage at the end of discharge because the Li content is less than 89% by mass.
[0160] When the negative electrode does not contain Mg, the improvement in the pulse discharge voltage at the end of the discharge phase due to the addition of metal element M is small (B1: 89 → B3: 91, B4: 92). In contrast, when the negative electrode contains Mg, the pulse discharge voltage at the end of the discharge phase is significantly improved by the addition of metal element M (B2: 100 → A2: 113, A4: 111). Therefore, it can be concluded that when the negative electrode (lithium alloy) contains Mg, the effect of suppressing the voltage drop at the end of the discharge phase due to the addition of metal element M can be significantly achieved.
[0161] As shown in Table 1, batteries A1 to A7, with a Mg content of 0.5% by mass and a combined Sr and Ba content of 0.00001 to 0.05% by mass, achieved high voltages at the end of discharge. Batteries A8 to A13, with a combined Sr and Ba content of 0.005% by mass and a Mg content of 0.01 to 10% by mass, also achieved high voltages at the end of discharge.
[0162] As shown in Table 3, batteries A14 to A18, which use Li-Mg-Sr-Ba-Al foil in the negative electrode, exhibit higher voltages at the end of discharge. For example, battery A11 (Li-Mg-Sr-Ba foil, Mg content: 1% by mass, Sr+Ba content: 0.005% by mass) has a pulse discharge voltage of 111, and battery A16 (Li-Mg-Sr-Ba-Al foil, Mg content: 1% by mass, Sr+Ba content: 0.005% by mass, Al content: 1% by mass) has a pulse discharge voltage of 114, further increasing the voltage at the end of discharge.
[0163] [Batteries A19~A26]
[0164] In the preparation of the non-aqueous electrolyte, additives were further incorporated into the non-aqueous electrolyte. The compounds shown in Table 4 were used as additives. The content (mass%) of the additives in the non-aqueous electrolyte was set to the values shown in Table 4.
[0165] In addition to the above, batteries A19 to A26 were manufactured in the same manner as battery A3 and were evaluated.
[0166] The evaluation results are shown in Table 4. In Table 4, the internal resistance is expressed as a relative value when the internal resistance of battery B2 is set to 100. The pulse discharge voltage is expressed as a relative value when the pulse discharge voltage of battery B2 is set to 100.
[0167]
[0168] As shown in Table 4, batteries A19~A26, which contain additives in non-aqueous electrolytes, exhibit a further decrease in resistance and a further increase in pulse discharge voltage during the final stage of discharge.
[0169] Industrial availability
[0170] The lithium primary battery disclosed herein can be well suited for use as a main power source or a backup power source for various instruments (e.g., smart meters for electricity, tap water, gas, etc.).
[0171] The present invention has been described with reference to preferred embodiments, but such disclosure should not be interpreted as restrictive. Various modifications and alterations will be readily apparent to those skilled in the art upon reading the above disclosure. Therefore, the appended claims should be interpreted as encompassing all modifications and alterations without departing from the true spirit and scope of the invention.
[0172] Explanation of reference numerals in the attached figures
[0173] 1: Positive electrode; 1a: Positive current collector; 2: Negative electrode; 3: Separator; 4: Positive electrode lead; 5: Negative electrode lead; 6: Upper insulating plate; 7: Lower insulating plate; 8: Sealing plate; 9: Battery casing; 10: Primary lithium battery.
Claims
1. A primary lithium battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode contains Li x MnO2, where, 0≤x≤0.05, The negative electrode comprises an alloy containing lithium, magnesium, and a metallic element M, wherein the metallic element M is at least one selected from strontium and barium. The lithium content in the alloy is 89% by mass or more. The magnesium content in the alloy is 0.01% by mass or more and 10% by mass or less. The content of the metallic element M in the alloy is more than 0.00001% by mass and less than 0.05% by mass.
2. The lithium primary battery according to claim 1, The alloy contains aluminum. The total content of magnesium and aluminum in the alloy is more than 0.02% by mass and less than 10% by mass.
3. The lithium primary battery according to claim 1, Li x The median particle size of MnO2 is greater than 5 μm and less than 40 μm.
4. The lithium primary battery according to claim 1, Li x The BET specific surface area of MnO2 is 5m². 2 / g or more and 40m 2 / g or less.
5. The lithium primary battery according to claim 1, The non-aqueous electrolyte contains at least one additive selected from cyclic imide compounds, phthalate compounds, and isocyanate compounds.
6. The lithium primary battery according to claim 5, The cyclic imide compound comprises at least one selected from phthalimide and N-substituted phthalimide.
7. The lithium primary battery according to claim 6, The N-substituted phthalimide comprises at least one selected from N-hydroxyphthalimide, N-(2-hydroxyethyl)phthalimide, N-(cyclohexylthio)phthalimide, and N-(phenylthio)phthalimide.
8. The lithium primary battery according to claim 5, The content of the cyclic imide compound in the non-aqueous electrolyte is less than 1% by mass.
9. The lithium primary battery according to claim 5, The phthalate compound includes a phthalate diester compound.
10. The lithium primary battery according to claim 9, The phthalate compound comprises dimethyl phthalate.
11. The lithium primary battery according to claim 5, The phthalate compound in the non-aqueous electrolyte is present in a concentration of less than 1% by mass.
12. The lithium primary battery according to claim 5, The isocyanate compound includes a diisocyanate compound.
13. The lithium primary battery according to claim 12, The diisocyanate compound comprises at least one selected from hexamethylene diisocyanate, 1,3-bis(isocyanate methyl)cyclohexane, and isophorone diisocyanate.
14. The lithium primary battery according to claim 5, The isocyanate compound in the non-aqueous electrolyte is present in an amount of less than 3% by mass.
Citation Information
Patent Citations
Lithium battery for high temperature use
JP2011192627A